Ice Breaking in Building a Learning Environment Active and Collaborative at Nur Syafi'il Ummah Vocational School - Ratnawati; Pupun Nuryani; Aryanti (Nexus Publishing NXP, 2024)
An active and collaborative learning environment has been proven to have benefits in increasing student motivation, participation and engagement. This article aims to analyze the use of ice breaking in building an active and collaborative learning environment. The approach used in writing this article is a descriptive qualitative approach using literature study methods through journals, scientific articles and book sources. Data analysis techniques involve data reduction, data visualization and inference steps. The results of this research on ice breaking show that ice breaking is effective in building an active and collaborative learning environment. In the studies and research reviewed, ice breaking has been proven to reduce students' initial anxiety and tension, create a relaxed atmosphere in the classroom, and increase communication and student involvement in the learning process.